Circular RNA WHSC1 exerts oncogenic properties by regulating miR‐7/TAB2 in lung cancer. Issue 20 (22nd September 2021) - Guan, Sisi; Li, Li; Chen, Wen‐Shu; Jiang, Wen‐Yang; Ding, Yun; Zhao, Li‐Lan; Shi, Yi‐Fan; Wang, Jun; Gui, Qi; Xu, Cheng‐Cheng; Cheng, Yang; Zhang, Wenjuan
Abstract: Circular RNA is a newly discovered member of non‐coding RNA (ncRNA) and regulates the target gene by acting as a micro‐RNA sponge. It plays vital roles in various diseases. However, the functions of circular RNA in non‐small cell lung cancer (NSCLC) remain still unclear. Our data showed that circ‐WHSC1 was highly expressed in NSCLC cells and tissues. Both in vitro and in vivo experiments showed that circ‐WHSC1 promoted NSCLC proliferation. circ‐WHSC1 also promoted the migration and invasion of lung cancer cells. Through bioinformatic analysis and functional experiments, we showed that circ‐WHSC1 could act as a sponge for micro‐RNA‐7 (miR‐7) and regulate the expression of TAB2 (TGF‐beta activated kinase one binding protein two). Inhibition of the circ‐WHSC1/miR‐7/TAB2 pathway could effectively attenuate lung cancer progression. In summary, this study confirmed the existence and oncogenic function of circ‐WHSC1 in NSCLC. The research suggests that the circ‐WHSC1/miR‐7/TAB2 axis might be a potential target for NSCLC therapy.